IMPLEMENTASI BANTUAN PERBAIKAN RUMAH TIDAK LAYAK HUNI BAGI MASYARAKAT BERPENGHASILAN RENDAH DI KOTA PADANG - Febri, Muhammad; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The background of the research based on communication problems between the implementation and the recipient of the House help is not feasible. Human resource limitation in assisting the recipient of home assistance is not habitable. Limited budgets for home repairs are not habitable. The research aims to determine the implementation of unhabitable home aid and see the inhibiting factors of implementation of home aid program is not habitable in Padang city. The concept of theory used is the implementation theory by Edward III (Widodo, 2011) namely: communication, resources, disposition, bureaucratic structure. The study uses qualitative methods with a phenomenological approach, with data collection techniques including: interviews, documentation and observations. The results of this study showed that the implementation of unfeasible home aid for low-income communities in Padang is not maximized. Factors that inhibit the communication performed by the implementation is not optimal,  limited human resources so that it is not optimal to assist beneficiaries, a limited budget for housing improvements is not livable. * Keywords : Policy, Implementation of Policy, Programs, Poor People